2016
DOI: 10.1037/bul0000040
|View full text |Cite
|
Sign up to set email alerts
|

Parsing fear: A reassessment of the evidence for fear deficits in psychopathy.

Abstract: Psychopathy is a personality disorder characterized by interpersonal manipulation and callousness, and reckless and impulsive antisocial behavior. It is often seen as a disorder in which profound emotional disturbances lead to antisocial behavior. A lack of fear in particular has been proposed as an etiologically salient factor. In this review, we employ a conceptual model in which fear is parsed into separate subcomponents. Important historical conceptualizations of psychopathy, the neuroscientific and empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(163 citation statements)
references
References 208 publications
12
150
0
1
Order By: Relevance
“…Related but distinct from anxiety, the genotypic link between fearlessness and boldness has been noted (Patrick et al, 2009) on the basis of Lykken's work (1957). Yet, others have reported that associations between conscious fear and psychopathy have been small and nonsignificant (Hoppenbrouwers et al, 2016). More work is needed to explicate the nexus between fearlessness, boldness, and low anxiety in the context of psychopathy.…”
Section: Underemphasis Of Boldness In the Capp And Ffm Psychopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Related but distinct from anxiety, the genotypic link between fearlessness and boldness has been noted (Patrick et al, 2009) on the basis of Lykken's work (1957). Yet, others have reported that associations between conscious fear and psychopathy have been small and nonsignificant (Hoppenbrouwers et al, 2016). More work is needed to explicate the nexus between fearlessness, boldness, and low anxiety in the context of psychopathy.…”
Section: Underemphasis Of Boldness In the Capp And Ffm Psychopathymentioning
confidence: 99%
“…Smith, Edens, & McDermott, ). Conceptually, boldness and its constituent elements are absent from, or have little emphasis in, several early depictions (e.g., McCord & McCord ; Robins, ) and historical syntheses of psychopathy (Hoppenbrouwers, Bulten, & Brazil, ; Werlinder, ). Further, a study of experts' perceptions found that a personality profile reflecting boldness traits was rated as weakly associated with psychopathy (Miller, Lamkin, Maples‐Keller, & Lynam, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fear refers to an emotion induced by a real or perceived threat that causes a change in metabolic and organ function and ultimately a change in behavior, including fleeing, fighting or hiding (Weiten and McCann, 2006). Fear has a conscious component that refers to the recognition of a threat and the negative valence that accompanies it, as well as an automatic component that refers to the response to the fear-related stimulus (Hoppenbrouwers et al, 2016). This response could be internal and physiological, like an increase in skin conductance and heart rate or an externalizing behavior such as freezing, fleeing or startling (Hoppenbrouwers et al, 2016).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 99%
“…Fear has a conscious component that refers to the recognition of a threat and the negative valence that accompanies it, as well as an automatic component that refers to the response to the fear-related stimulus (Hoppenbrouwers et al, 2016). This response could be internal and physiological, like an increase in skin conductance and heart rate or an externalizing behavior such as freezing, fleeing or startling (Hoppenbrouwers et al, 2016). The fear center of the brain is thought to be the amygdala, one of the major structures of the limbic system (LeDoux, 2003).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 99%
“…The most common finding in the literature is that psychopathic individuals experience difficulties in learning to avoid punishment in laboratory settings (Blair, 2005;Blair et al, 2004;Newman & Schmitt, 1998). The consistent findings of reduced passive avoidance learning and reduced responses to punishment have been discussed as evidence for the relevance of trait fearlessness to psychopathy (Hoppenbrouwers, Bulten, & Brazil, 2016).…”
Section: Psychopathy and Emotionmentioning
confidence: 99%